Implementasi Community-Based Legal Education sebagai Upaya Pencegahan Kekerasan terhadap Perempuan dan Anak di Desa Keraton - Leliya; Muhamad Mujahidin (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2026)
Violence against women and children in rural Indonesia reflects structural inequalities, patriarchal norms, and low legal literacy, resulting in a persistent gap between law in the books and law in action. This study analyzes the effectiveness of Community-Based Legal Education (CBLE) as a preventive strategy in Keraton Village, Cirebon Regency. Employing a quasi-experimental design with a pre-post intervention approach within a Participatory Action Research framework, the study involved 50 purposively selected participants. Data were collected through legal literacy tests, interviews, focus group discussions, and participatory observation, and analyzed using descriptive statistics and thematic analysis. The findings demonstrate a significant increase in legal literacy scores from 48 to 84, accompanied by shifts in collective perceptions of violence from a private matter to a public legal issue. The intervention also strengthened social capital and institutionalized prevention mechanisms through the establishment of a Community for Women and Child Protection. The study concludes that CBLE is an effective empowerment-based preventive model, although its sustainability depends on policy integration and consistent village governance support.